2005
DOI: 10.1590/s1415-52732005000400004
|View full text |Cite
|
Sign up to set email alerts
|

Estado nutricional e anemia ferropriva em gestantes: relação com o peso da criança ao nascer

Abstract: OBJETIVO: Avaliar o estado nutricional e a prevalência de anemia durante a gestação e correlacioná-los com o peso do recém-nascido. MÉTODOS: Foi realizado estudo transversal com gestantes que realizaram o pré-natal no único serviço público de saúde do município de Viçosa, MG, no período de dezembro de 2002 a maio de 2003. Foi aplicado questionário com informações maternas e realizada dosagem de hemoglobina através do Hemocue, além da obtenção de dados de peso e estatura da gestante. As informações referentes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0
41

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 13 publications
3
14
0
41
Order By: Relevance
“…The linear regression analysis showed that the only maternal variable associated with the birth weight was the total weight gain during pregnancy, a result that can be justified by the low frequency of children with low birth weight, since other studies have found a positive correlation between birth weight and maternal pre-gestational height, weight and BMI, as well as total weight gain (4,20) .…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The linear regression analysis showed that the only maternal variable associated with the birth weight was the total weight gain during pregnancy, a result that can be justified by the low frequency of children with low birth weight, since other studies have found a positive correlation between birth weight and maternal pre-gestational height, weight and BMI, as well as total weight gain (4,20) .…”
Section: Discussionmentioning
confidence: 88%
“…Although many studies emphasize excessive weight gain as an issue that requires immediate attention in the prenatal services (3)(4)(8)(9)11,(17)(18) , the finding that a high percentage of pregnant women presented insufficient weight gain (36.4%) is also disturbing, a situation that is associated with increased risk of premature birth and low birth weight (4,20) . These findings reinforce the importance of nutritional monitoring in the prenatal period, which should focus on modifiable variables, such as weight gain and the diet, and benefits women at risk of both excessive and insufficient weight gain (21) , through the monitoring of weight gain and guidance on healthy eating practices (1) .…”
Section: Discussionmentioning
confidence: 99%
“…No Brasil, pesquisas que investigam o tema alimentação na gestação priorizam metodologias quantitativas com objetivo de avaliar o estado nutricional materno, o ganho de peso gestacional e a associação com variáveis de interesse 3,4,5 . De forma menos constante, alguns estudos incorporam o conhecimento das crenças, proibições e prescrições que interferem no comportamento e nas práticas alimentares de gestantes, puérperas e lactantes 6,7,8 .…”
Section: Pregnancy; Feeding Behavior; Qualitative Researchunclassified
“…Prematurity, low birth weight, and higher maternal and perinatal mortality rate stand out as harmful consequences of anemia during the gestational period 1,[6][7][8] . Recognizing the negative effects of anemia on health and survival of the mother and child, the Brazilian Ministry of Health implemented drug iron supplementation in the Programa de Atenção à Gestante (Health Care Program for Pregnant Women) in 1982 9 and subsequently in the Programa Nacional de Suplementação de Ferro (National Iron Supplementation Program) in 2005 10 .…”
Section: Introductionmentioning
confidence: 99%